2001
DOI: 10.1248/cpb.49.1555
|View full text |Cite
|
Sign up to set email alerts
|

Two New 2'-Oxygenated Flavones from Andrographis elongata.

Abstract: Andrographis elongata T. And (Acanthaceae) is an herbaceous plant distributed throughout the Western Ghats of South India.1) As part of our continuing investigation on the flavonoid constituents of Andrographis species, [2][3][4][5][6] we have examined the whole plant of A. elongata, a plant hitherto not investigated for its chemical constituents and report here the isolation and structure elucidation of two new 2Ј-oxygenated flavones (3, 5), in addition to three known flavones (1, 2, 4). Results and Discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…244 A crude extract of leaves and twigs of Piper longicaudatum (Piperaceae) showed antibacterial activity towards Staphylococcus aureus and methicillin-resistant S. aureus. The active fraction yielded the new longicaudatin (114) and three known dihydrochalcones, including asebogenin (4,2Ј,6Ј-trihydroxy-4Јmethoxydihydrochalcone). 245 However, only asebogenin showed inhibitory activity against the two bacterial strains (IC 50 of 10 and 4.5 µg ml Ϫ1 , respectively).…”
Section: Lipophilic Flavones and Flavonolsmentioning
confidence: 99%
“…244 A crude extract of leaves and twigs of Piper longicaudatum (Piperaceae) showed antibacterial activity towards Staphylococcus aureus and methicillin-resistant S. aureus. The active fraction yielded the new longicaudatin (114) and three known dihydrochalcones, including asebogenin (4,2Ј,6Ј-trihydroxy-4Јmethoxydihydrochalcone). 245 However, only asebogenin showed inhibitory activity against the two bacterial strains (IC 50 of 10 and 4.5 µg ml Ϫ1 , respectively).…”
Section: Lipophilic Flavones and Flavonolsmentioning
confidence: 99%
“…As reported by Li et al [6] 14-hydroxy of andrographolide is rearranged to form isoandrographolide, which is chemically more stable than andrographolide. Flavones like 7-O-methylwogonin and skullcapflavone-I have been reported to be isolated from the whole plant of A. elongata [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was recognised as a flavonoid with 3-or 5-, or orthodihydroxyl groups from its colour reaction in the 2% AlCl 3 /EtOH test. The UV absorption of 1 in MeOH (254 and 348 nm) and a bathchromic shift of 38 nm with AlCl 3 /HCl suggested that it is a 5-hydroxyflavone compound [3,4]. In addition, it gave also characteristic diagnosis of glycoside from its positive reactions to the a-naphthol and the absorption bands at n max 1480-1010 (O-glycosyl) cm 21 in the IR spectrum.…”
Section: Resultsmentioning
confidence: 98%